ECONOMIC EFFECTIVENESS OF INVESTMENTS IN FRUIT TREE NURSERIES - Gogić, Petar; Ivanovic, Sanjin M. (Poslovna ekonomija, 2018)
ABSTRACT: In order to develop and improve fruit production in Serbia it is necessary to invest in establishment of nurseries for production of quality fruit seedlings. Therefore the goal of this paper is to analyze economic efficiency of investments in fruit nurseries. Discounting methods of investment evaluation (Net Present Value, Internal Rate of Return and Payback period) are used to determine profitability of investments in expected circumstances while sensitivity analysis and scenario analysis methods were used to evaluate investments in risky circumstances. It is determined that investments in fruit nurseries are economically efficient even in risky circumstances. Type of nurseries which provide more balanced cash flows is more economically efficient and less risky.